The first French reformation: church reform and the origins of the old regime - Lange, Tyler (Cambridge University Press, 2014)
The political culture of absolute monarchy that structured French society into the eighteenth century is generally believed to have emerged late in the sixteenth century. This new interpretation of the origins of French absolutism, however, connects the fifteenth-century conciliar reform movement in the Catholic Church to the practice of absolutism by demonstrating that the monarchy appropriated political models derived from canon law. Tyler Lange reveals how the reform of the Church offered a crucial motive and pretext for a definitive shift in the practice and conception of monarchy, and explains how this first French Reformation enabled Francis I and subsequent monarchs to use the Gallican Church as a useful deposit of funds and judicial power. In so doing, the book identifies the theoretical origins of later absolutism and the structural reasons for the failure of French Protestantism.